Numerical analysis of peristaltic blood flow in arteries - Paszyński, Maciej; Pele, Andrzej (Computer Assisted Methods in Engineering and Science, 2001)
The problem of blood flow in arteries induced by peristaltic waves has been investigated. The methodology of modelling global circulation system has been outlined. Medical measurements required for problem formulation have been presented. Numerical solutions of blood flow in artery based on finite element method have been worked out. The paper presents local model of pulsatile blood flow in the human artery. Modelling of pulsatile flow in cardiovascular system could improve understanding and interpretation of flow measurements in arteries locally as well as ventricular- vascular interaction in healthy patients at rest and while exercising. Results achieved on local models could be generalized to formulate a global model of haemodynamics of cardiovascular system in man. This approach could help identifying physiology of optimal heart work at rest, physical activity and also in pathological conditions as hypertension, cardiac insufficiency, heart defects, coronary heart disease and origin and progression of artherosclerosis as well.